2012
DOI: 10.1108/14725961211200397
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to successful public private partnership projects

Abstract: Purpose -With the increasing interest in public private partnership (PPP), there is a need to investigate the factors contributing to successful delivery of PPP projects. The purpose of this paper is to analyze the perceptions of respondents from Hong Kong, Australia and the UK on the importance of 18 such factors. Design/methodology/approach -An empirical questionnaire survey was conducted in Hong Kong and Australia. The survey respondents were asked to rate 18 factors which contribute to delivering successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 14 publications
7
121
0
2
Order By: Relevance
“…Measures of political factor are a stable political environment, government support for public housing, government guarantees, a favourable legal framework, provision of land with secure tenure, adequate funding of infrastructure by the government and finally, government support for local building materials manufacturers. This result is consistent with that of Hwang and Lim (2013) and Cheung, Chan and Kajewski (2012) who stress the importance of a stable political environment in successful implementation of projects. To encourage the private sector to invest in public housing projects, the government should provide a guarantee to developers by managing those risks that the government is in the best position to handle, such as fluctuation of the exchange rate and changes in law.…”
Section: Discussionsupporting
confidence: 91%
“…Measures of political factor are a stable political environment, government support for public housing, government guarantees, a favourable legal framework, provision of land with secure tenure, adequate funding of infrastructure by the government and finally, government support for local building materials manufacturers. This result is consistent with that of Hwang and Lim (2013) and Cheung, Chan and Kajewski (2012) who stress the importance of a stable political environment in successful implementation of projects. To encourage the private sector to invest in public housing projects, the government should provide a guarantee to developers by managing those risks that the government is in the best position to handle, such as fluctuation of the exchange rate and changes in law.…”
Section: Discussionsupporting
confidence: 91%
“…Li et al (2005) also identified five key PPP success factors as: (1) strong private consortium; (2) appropriate risk allocation and risk sharing; (3) available financial market; (4) commitment/responsibility of public/private sectors; and (5) thorough and realistic cost/benefit assessment. Additionally, the commitment and shared vision, open communication and trust, and collaboration are the three key PPP success factors identified in the United States of America by Jacobson and Choi (2008), whereas, in China, the key success factors for PPP projects are a stable macro-economic condition; favourable legal framework; sound economic policy; available financial market; and multi-benefit objectives (Cheung, Chan and Kajewski, 2012). A stable macro-economic condition is seen as an important factor in the delivery of PPP project successfully in the country, although, China is still being recognized as a developing country, despite the large size of her economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, this is a concept being adopted in the construction industry (Sanvido et al, 1992;Chua, Cog and Loh, 1999). The concept of critical success factors has been investigated by many authors on PPP projects (Jefferies, Gameson and Rowlinson, 2002;Li et al, 2005;Cartligde, 2006;Jacobson and Choi, 2008;Cheung, 2009;Agrawal, 2010;Minnie, 2011;Chou et al, 2012;Ng, Wong and Wong, 2012;Cheung, Chan and Kajewski, 2012;Tang et al, 2013;Ismail, 2013;Wibowo and Alfen, 2014;and Ameyan and Chan, 2015). A comprehensive literature review was conducted to identify CSFs of PPP in the construction industry.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, project success is examined from the perspective of the owners. Project success is the degree to which project goals and expectations are met [50,51].…”
Section: Project Successmentioning
confidence: 99%